Acute toxicity of triazine pesticides to juvenile signal crayfish (Pacifastacus leniusculus) - Velisek, Jozef; Kouba, Antonin; Stara, Alzbeta (Neuro endocrinology letters, 2013)
OBJECTIVES: Crustacea are at high risk of toxic effects of agricultural pesticides. Currently, many questions regarding the toxicity of triazine herbicides to crayfish remain unresolved. The aim of this research was to evaluate the acute toxicity of atrazine, hexazinone, metribuzine, prometryne, simazine, and terbutryne to juvenile signal crayfish (Pacifastacus leniusculus). DESIGN: Acute toxicity tests were performed in accordance with standardized guidelines for testing of chemicals, OECD no. 203, using a semistatic test system. Signal crayfish juveniles (n=672) of 49.0-81.5 mg weight and 12.8-16.0 mm total length were used for the bioassay. Mortalities were recorded daily to 96 h. Each pesticide was tested at concentrations of 1, 10, 40, 70, and 100 mg.l-1. Percent mortalities were analyzed by linear regression, and median lethal concentration (LC50) values were computed using probit analysis EKO-TOX 5.2 software. RESULTS: 96hLC50 values for juvenile signal crayfish were 12.1 mg.l-1 for atrazine, 13.9 mg.l-1 for terbutryne, 14.4 mg.l-1 for prometryne, 19.5 mg.l-1 for hexazinone, 30.6 mg.l-1 for metribuzine, and 77.9 mg.l-1 for simazine. Atrazine showed the greatest toxicity to signal crayfish. CONCLUSIONS: The present study demonstrated that triazines are toxic to signal crayfish. Signal crayfish is more sensitive than the fish for atrazine, hexazine, metribuzine, and for these triazines signal crayfish can be used as a bio-indicator of environmental contamination.
Keywords: testy akutní toxicity; Pesticides; pohybová aktivita; triaziny; Dose-Response Relationship, Drug; Triazines; severní raci; vztah mezi dávkou a účinkem léčiva; Animals; Behavior, Animal; chování zvířat; pesticidy; Astacoidea; Motor Activity; zvířata; Toxicity Tests, Acute